PREOPERATIVE EDUCATION AND PARENTAL ANXIETY: INVESTIGATING POSTOPERATIVE OUTCOMES AMONG PARENTS OF PEDIATRIC PATIENTS IN PESHAWAR (The Research of Medical Science Review, 2025)
Background of the study: Congenital heart defects (CHD) affect approximately 1.3 million newborns annually, with 70% requiring medical or surgical intervention. Parents of these children often experience significant anxiety, which can be mitigated through preoperative education. However, this practice is not widely implemented in Pakistan. This study evaluates the effectiveness of preoperative education in reducing postoperative parental anxiety. Methodology: A quantitative study was conducted in Peshawar, Pakistan, involving 50 parents of children undergoing cardiac surgery. Data was collected using the State Anxiety Inventory pre- and postoperatively. A convenient sampling technique was employed. Results: Postoperative anxiety scores (μ=29.3) were significantly lower than preoperative scores (μ=69.7), demonstrating the positive impact of preoperative education. Among participants, 62% were female, 40% were literate, and 60% were employed. A significant proportion (82%) had a monthly income below 50,000 PKR. Conclusion: Preoperative education effectively reduces parental anxiety post-surgery. Implementing structured educational programs can enhance parental well-being and support children's recovery.